Early Detection and Quantitative Analysis of Skin Cancer Using THz Metamaterial Biosensor - Qureshi, Suhail Asghar; Zainal Abidin, Zuhairiah; Kamarudin, Muhammad Ramlee; Ghazali, Nurul Bashirah (International Journal of Integrated Engineering, 2024)
Terahertz imaging offers significant potential for the early detection of skin cancer. This study introduces a metamaterial unit cell designed to operate in the terahertz (THz) band for non-invasive contact-based skin cancer detection. The sensor relies exclusively on the reflection coefficient response, providing high sensitivity to subtle changes in tissue properties without requiring complex signal processing. This simplicity may result in a cost-effective and straightforward implementation for early cancer detection. Simulations were conducted using 3D models representing various skin types, including normal skin, basal cell carcinoma (BCC), and melanoma. The dielectric characteristics of the samples were determined using the Double Debye model. The simulations revealed that the metamaterial design exhibited double negative material properties at a specific frequency of 1.15 THz. Upon skin contact and detection of malignancy, the reflection coefficient showed a shift toward lower frequencies. Notably, the melanoma sample exhibited the most significant shift, indicating a more severe form of cancer compared to BCC. Furthermore, it was observed that the difference in resonance frequencies between normal and malignant skin increased with the thickness of the sample. The sensor demonstrated high sensitivity in detecting cancer thickness, with a sensitivity of 9.25 GHz/µm for basal cell carcinoma (BCC) and 10.2 GHz/µm for melanoma. Furthermore, linear regression analysis revealed a robust correlation between the resonance frequency and the variation in cancer thickness, with R2 values of 0.9948 and 0.9947 for BCC and melanoma, respectively. These findings underscore the sensor's ability to detect skin cancer at its earliest stages, regardless of its severity.